How do socioeconomic determinants of health affect the likelihood of living with HTLV-1 globally? A systematic review with meta-analysis - Ramesh, Nydile; Cockbain, Beatrice; Taylor, Graham P.; Rosadas, Carolina (Frontiers in Public Health, 2024)
Introduction Human T Lymphotropic Virus type 1 (HTLV-1) is a neglected retrovirus associated with many clinical disorders, most notably Adult T-cell Leukemia/Lymphoma and HTLV-1-Associated Myelopathy (HAM). Found in endemic clusters across the world, high prevalence has been reported in minoritized groups who suffer from health inequities. This study investigates the association between HTLV-1 prevalence and the following socioeconomic determinants of health: education, income, and employment, which are markers of health inequity. Methods A systematic review was conducted by searching the following databases: Ovid/Medline, Embase, Global Health Database, Web of Science, LILACS and SciELO. Primary studies in English, Spanish and Portuguese mentioning HTLV-1 and one of education, income and/or employment were included. A random-effects meta-analysis was performed, and odds ratios (OR) were calculated to determine the association between these socioeconomic determinants of health and HTLV-1 prevalence. Results 42 studies were included. The likelihood of having HTLV-1 was higher in individuals with less than completed primary education compared to those who completed primary education (OR 1.86 [95% CI 1.34–2.57]; p < 0.01). This may be because individuals with low education have reduced access to and understanding of health information, thus increasing the prevalence of risk factors associated with HTLV-1 infection. No other determinants were found to be statistically significant. Conclusion Fewer years of schooling are associated with increased likelihood of contracting HTLV-1. Therefore, health promotion materials and public health policies regarding HTLV-1 must consider those with lower educational levels to effectively reduce disease transmission. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=335004, identifier (CRD42022335004).